Marshall Immersion Performance of Asphalt ConcreteBinder Course with Silica Sand as Fine Aggregate Substitute - Lusyana, Lusyana; Mukhlis, Mukhlis; Suardi, Enita; Khairunnisa, Latifa; Huzzairi, Muhammad (ABEC Indonesia, 2024)
The Asphalt Concrete Binder Course (AC-BC) layer is part of the pavement structure that serves as an intermediate layer to withstand the maximum load from traffic. Damage to the pavement layer, which often occurs on the surface, can be influenced by layers with large pores and voids due to inadequate compaction during construction. In large voids, water can enter the pavement structure through cracks and gaps, forming potholes. Water trapped within the pavement structure can accelerate road deterioration, reducing the pavement layer’s ability to support traffic loads. The purpose of using silica waste in this study is to assess the Marshall Immersion performance (water resistance) of the AC- BC mixture with silica sand. Variations of the AC-BC mixture using silica sands as a fine aggregate substitute include SI- 0%, SI-25%, SI-50%, SI-75%, and SI-100%. The Marshall Immersion test was conducted by continuously immersing the samples in water for 0.5 hours, 24 hours, and 48 hours. To assess the Marshall Immersion performance of the AC-BC asphalt mixture, two indicators were used: the Index of Retained Stability (IRS) and the Index of First Durability (IDF). From the study, the IRS values obtained were as follows: SI-0%; 92.53%, SI-25%; 92.42%, SI-50%; 91.56%, SI-75%; 91.21%, and SI-100%; 90.78%. These results overall indicate that with silica sand substitution, the IRS values decrease but still meet the minimum requirement of 90%. The IDF values (r%) were positive (+). This positive value indicates that some mixture variations experienced different degrees of strength loss.